Frequency of de novo variants and parental mosaicism in families with inactivating PTH/PTHrP signaling disorder type 2 - Vado, Yerai; Pereda, Arrate; Manero-Azua, Africa; , Spanish Network for Imprinting Disorders; Perez de Nanclares, Guiomar (Frontiers in Endocrinology, 2023)
Objective iPPSD2 (which includes PHP1A and PPHP/POH) is a rare inherited autosomal dominant endocrine disorder caused by inactivating GNAS pathogenic variants. A high percentage of de novo cases has been suggested. In rare cases, parental mosaicism has been described, but its real frequency is unknown. Design A retrospective study including a series of 95 genetically confirmed iPPSD2 probands. Methods The frequency of de novo cases was evaluated and the distribution of the type of variants was compared according to the type of inheritance. The putative involved allele was determined by reverse transcriptase PCR (RT-PCR) or allele specific oligonucleotide RT-PCR (ASO-RT-PCR). The possibility of GNAS mosaicism was studied by next-generation sequencing (NGS) on the corresponding parental DNA. Results In 41 patients the variant was of de novo origin and in 24 the origin could not be established. In both cases 66.67% of variants generated a truncated or absent protein whereas the rest of the variants were missense or in-frame deletion/duplication. Parental origin was studied in 45 of those patients and determined in 35. Curiously, the percentage of de novo variants at the paternal allele was higher than when paternally inherited (31.1% vs 6.67%). NGS detected mosaicism in three independent families: one from paternal DNA (allelic ratio 10%) and two from maternal DNA (allelic ratio 10% and 2%). Conclusion De novo pathogenic variants are frequent in iPPSD2 (around 45%). Parental mosaicism is infrequent (8.11%) but should be analyzed with NGS, taking into account its importance in genetic counselling.